A diketopyrrolopyrrole-based macrocyclic conjugated molecule for organic electronics. Issue 13 (8th March 2019) - Li, Cheng; Wang, Chao; Guo, Yiting; Jin, Yingzhi; Yao, Nannan; Wu, Yonggang; Zhang, Fengling; Li, Weiwei
Abstract : The first diketopyrrolopyrrole based donor–acceptor macrocyclic conjugated molecule was developed and its application in organic electronics was systematically studied. Abstract : In this work, the first diketopyrrolopyrrole (DPP) based donor–acceptor macrocyclic conjugated molecule was developed and its application in organic electronics was systematically studied. Macrocyclic molecules, as a fragment of armchair carbon nanotubes, have emerged as functional materials in materials chemistry, but the materials are always limited to cycloparaphenylenes. Using the donor–acceptor design strategy that has been widely used in high performance conjugated polymers for macrocyclic molecules, it will significantly broaden their species with tunable optical and electrical properties. Herein, we synthesize a well-defined macrocyclic molecule containing four electron-deficient DPP units alternating with electron-rich thiophenes. The new molecule was found to show high solubility, near-infrared absorption spectra and 3D charge transport properties. The new macrocyclic molecule as an electron acceptor was applied to non-fullerene organic solar cells, exhibiting an initial efficiency of 0.49%, while the linear molecule with a similar backbone only showed a very low efficiency of 0.03%. Our results demonstrate that donor–acceptor macrocyclic conjugated materials have great potential application in organic electronics.